Processing of Namwa Bananas (Musa sapientum Linn.) Dried using Greenhouse Solar Dryer and Automatic Control of Supplementary Heat System Huai Nam Rin Royal Project Development Center, Chiang-rai Province, Thailand - Assawarachan, Rittichai (Area Based Development Research Journal, 2024)
Implementing the pilot reforestation voluntary project for greenhouse gas reduction at the Huai Nam Rin Royal Project Development Center in Wiang Pa Pao District, Chiang Rai Province, Thailand involved the distribution of organic banana shoots to highland farmers to replace corn cultivation. However, the project faced challenges due to the low selling price of Namwa bananas (Musa sapientum Linn.) and the high cultivation costs. Farmers were selling bananas in bulk at an average price of only 4.84 Baht (around 0.14 USD) per kg, which was insufficient for their livelihood. The problem was originated from a lack of knowledge and innovation for processing bananas to add value and extend the shelf life. To address this, the project developed a greenhouse solar dryer and automatic control of supplementary heat system and conducted a workshop on processing dried bananas according to Thailand Industry Standard-S. After the workshop, 19 farmers established the Community Enterprise Group, Agricultural Product Processing Group Ban Huai Muang-Pong Nam Ron-Muang Noi to produce and sell banana sticks and rolled products. As a result, the selling price of fresh Namwa bananas increased to 8 Baht (around 0.23 USD) per kilogram, leading to an average annual income increase of 22,758 Baht (around 664 USD) per family, which provided sufficient income for their livelihood. Additionally, farmers have become more attentive to caring for the banana plants, resulting in a higher survival rate. A total of 4,200 banana plants are now thriving across 36 acres, with a survival rate of 58.33%. Processed banana products are additionally developed in the form of banana beverages and expanded to products made from other fruits. The project’s success contributes to environmental sustainability, enabling farmers to be self-reliant and recognize the value of sustainable agricultural practices.